Bioethics in Education - Γλυκοφρύδη (Alexandra Glykofridi), Αλεξάνδρα; Ζαπουνίδου (Maria Zapounidou), Μαρία (Bioethica, 2019)
During recent years, bioethics have become increasingly important as it has become clear that citizens of all ages will be called upon to take ethical decisions about the use of science and technology at some stage of their lives. Research shows that there is a global agreement on the need to teach more of these ethical and social issues related to science and technology at all levels of education. This article attempts to investigate the importance and role of bioethics in secondary and undergraduate university education. Examples of primary and secondary education curricula, their goals and their contribution to improving students' understanding of the different aspects of bioethics are presented. Then, it is attempted to review the situation of bioethics in universities curricula. The article analyzes the different philosophies of approaching bioethical education, its relation with human rights and compares the advantages and disadvantages of the teaching strategies of integration and specialization. In conclusion, it seems that bioethics is worthwhile being joined together with other disciplines and integrated into a wider framework of effective and informed decision-making skills, whether the person is a health professional or a modern citizen.